Investigation of the Influence of the Nature of the Solvent on the Properties of Solutions of Grafted Triacetate Copolymers (Texas Journal of Multidisciplinary Studies, 2022)
In our urbanized rapidly developing world, interest in an extensive class of organic polymers, and methods of grafting various vinyl monomers to them, has increased dramatically, which affects the physicochemical properties of the polymers themselves, and polymer materials, thus giving Cellulosic materials a number of valuable properties and expanding the scope of their application.